2016
DOI: 10.1002/advs.201600319
|View full text |Cite
|
Sign up to set email alerts
|

A 3D Chemically Modified Graphene Hydrogel for Fast, Highly Sensitive, and Selective Gas Sensor

Abstract: Reduced graphene oxide (RGO) has proved to be a promising candidate in high‐performance gas sensing in ambient conditions. However, trace detection of different kinds of gases with simultaneously high sensitivity and selectivity is challenging. Here, a chemiresistor‐type sensor based on 3D sulfonated RGO hydrogel (S‐RGOH) is reported, which can detect a variety of important gases with high sensitivity, boosted selectivity, fast response, and good reversibility. The NaHSO3 functionalized RGOH displays remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
107
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(108 citation statements)
references
References 56 publications
1
107
0
Order By: Relevance
“…Polyaniline sensors detect 40 ppb NH 3 at ≥90% RH,9 but these are usually for single‐use only as they recover too slowly. Other polymers like PEDOT:PSS nanowires feature higher LODs of 100 ppb,10 which is even higher for carbon‐based reduced graphene oxide (1.2 ppm in dry air)11 and 3D sulfonated reduced graphene oxide hydrogels (1.5 ppm) 12. Finally, metal‐oxides can also detect sub‐ppm NH 3 concentrations (e.g., Si‐doped MoO 3 with LODs of 51 ppb at 90% RH25 and pure MoO 3 of 280 ppt in dry air26) but these require typically elevated operational temperatures (e.g., 400–450 °C).…”
Section: Resultsmentioning
confidence: 99%
“…Polyaniline sensors detect 40 ppb NH 3 at ≥90% RH,9 but these are usually for single‐use only as they recover too slowly. Other polymers like PEDOT:PSS nanowires feature higher LODs of 100 ppb,10 which is even higher for carbon‐based reduced graphene oxide (1.2 ppm in dry air)11 and 3D sulfonated reduced graphene oxide hydrogels (1.5 ppm) 12. Finally, metal‐oxides can also detect sub‐ppm NH 3 concentrations (e.g., Si‐doped MoO 3 with LODs of 51 ppb at 90% RH25 and pure MoO 3 of 280 ppt in dry air26) but these require typically elevated operational temperatures (e.g., 400–450 °C).…”
Section: Resultsmentioning
confidence: 99%
“…C) 3D chemically modified graphene hydrogel. Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Hydrogels For Environmental Applicationsmentioning
confidence: 99%
“…Graphene present in the hydrogel, which comes with defects and functionalities, has shown to have a better adsorption energy for NO 2 than NH 3 . The same group then went on to improve this graphene‐based composite, employed with a microheater and functionalizing it with NaHSO 3 , found that the responses increased 118.6, and 58.9 times for NO 2 and NH 3 , respectively (Figure C) . This sulfonated‐graphene hydrogel was also found to have a high responsivity for volatile organic compounds.…”
Section: Hydrogels For Environmental Applicationsmentioning
confidence: 99%
“…Different from the traditional inorganic aerogels which is brittle, the CNT and graphene aerogels can be endowed with good flexibility, compressibility, and even stretchability by structural design . Moreover, because of the high degree of graphitization, the CNT and graphene aerogels possess superior thermal and chemical stability, and electrical properties than common carbon aerogels and can be used in many fields . As a supporting material, carbon aerogel can supply a 3D porous and electrically conductive network for fast mass transport and electron transfer, and large surface area for the depositing and avoiding the ripening and aggregation of active particles .…”
Section: Preparation and Classification Of Aerogelsmentioning
confidence: 99%
“…Graphene is a promising candidate for the gas sensors for detecting individual gas due to its exceptionally low‐noise property, however, the graphene‐based sensors without any modification always exhibit an inferior selectivity . The chemical modification and introduction of heterostructure materials in the 3D graphene network have been proved to be efficient ways to prepare high‐performance gas sensors . For example, HSO 3 − with lone‐pair electrons was used to modify the graphene sheets, and the resultant modified graphene network showed an enhanced selectivity of NO 2 due to the weak interaction between HSO 3 − and NO 2 .…”
Section: Aerogel‐based Sensorsmentioning
confidence: 99%